DIFFERENCES IN BLOOD GLUCOSE LEVELS BETWEEN INDIVIDUALS WHO ARE USUALLY CONSUMING WARM RICE AND COLD RICE IN DEMBE JAYA VILLAGE, NORTH KOTA DISTRICT, GORONTALO CITY (Journal of Health, Technology and Science (JHTS), 2025)
Freshly cooked, warm rice has a higher carbohydrate content than cold rice, as the glycemic index of cold rice tends to be lower. Therefore, consuming cold rice does not immediately increase blood sugar levels. Glucose in food is a simple carbohydrate from the monosaccharide group obtained from the hydrolysis of starch. Several factors influence the carbohydrate and glucose content of rice, including the type of rice, processing method, and storage method. This research approach was quantitative, with a cross-sectional design and comparative quantitative approach. A sample size of 30 was selected using a purposive sampling technique. Blood glucose testing used a POCT (Point of Care Testing) device. Based on the results of the Shapiro-Wilk normality test, the blood glucose levels in the group consuming warm rice had a significance value of
Keywords: Warm Rice, Cold Rice, Blood Glucose